THE EXISTENCE OF REQUEST CIVIL OF REGIONAL OFFICERS WHOSE SCOPE OF DECISONS ARE APPLICABLE IN THE REGIONAL AREA - Siti Latifah; Rr. Herini Siti Aisyah; Xavier Nugraha (International Journal of Economics, Business and Accounting Research (IJEBAR), 2021)
From Article 45A paragraph (1) jo. Paragraph (2) of Law 5/2004, it can be understood that a state administrative case whose object of lawsuit is a decision of a regional official whose decision range is valid in the region concerned cannot be filed for cassation, but things that are not regulated are related about request civil. Based on the background above, it can be understood that the formulation of the problem in this article are: 1) Limitation of legal remedies against state administrative cases where the object of the lawsuit is a regional official's decision whose range of decisions applies to regional areas; and 2) Legal remedies to review state administrative cases where the object of the lawsuit is a decision by a regional official whose decision range is valid in a regional area. This research is legal research with statute approach and conceptual approach. Based on this research, it was found that Firstly The limitation of legal remedies against state administrative cases where the object of the lawsuit is in the form of a regional office's decision whose range of decisions applies to regional areas is that an appeal cannot be filed and Secondly there is no prohibition at all regarding legal remedies for request civil